Rotational piezoelectric energy harvesting: A comprehensive review on excitation elements, designs, and performances - Chilabi H.J.; Salleh H.; Al-Ashtari W.; Supeni E.E.; Abdullah L.C.; Asarry A.B.; Rezali K.A.M.; Azwan M.K. (MDPI AG, 2023)
Air; Availability; Frequency converters; Gravitation; Piezoelectricity; Centrifugal Forces; Compact designs; Frequency up conversion; Gravity forces; Magnetic force; Natural environments; Output power density; Piezoelectric energy harvesting; Energy harvesting